2021
DOI: 10.3389/fpls.2021.625729
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis Reveals Opposite Effects of Biotic and Abiotic Stresses on Transcript Levels of Arabidopsis Intracellular Immune Receptor Genes

Abstract: Plant intracellular immune receptor NLR (nucleotide-binding leucine-rich repeat) proteins sense the presence of pathogens and trigger strong and robust immune responses. NLR genes are known to be tightly controlled at the protein level, but little is known about their dynamics at the transcript level. In this study, we presented a meta-analysis of transcript dynamics of all 207 NLR genes in the Col-0 accession of Arabidopsis thaliana under various biotic and abiotic stresses based on 88 publicly available RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 90 publications
(107 reference statements)
0
19
0
Order By: Relevance
“…Despite the findings of the differences in the number of yield-related genes among the different N-responsive transcriptomic data sets generated under different growth and treatment conditions, taking them together, we identified 1,064 genes as both N-responsive and yield-related. Meta-analysis allows such identification from diverse data sets as reported earlier for Arabidopsis (Zhang et al, 2020a ; Yang et al, 2021 ) and rice (de Abreu-Neto and Frei, 2016 ; Muthuramalingam et al, 2017 ; Cohen and Leach, 2019 ; Kong et al, 2019 ). In order to minimize variations in data processing, we used uniform selection criteria (Log 2 FC ≥ 1, value of p ≤ 0.05) with a default redundancy removal setting for all the microarray data sets.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the findings of the differences in the number of yield-related genes among the different N-responsive transcriptomic data sets generated under different growth and treatment conditions, taking them together, we identified 1,064 genes as both N-responsive and yield-related. Meta-analysis allows such identification from diverse data sets as reported earlier for Arabidopsis (Zhang et al, 2020a ; Yang et al, 2021 ) and rice (de Abreu-Neto and Frei, 2016 ; Muthuramalingam et al, 2017 ; Cohen and Leach, 2019 ; Kong et al, 2019 ). In order to minimize variations in data processing, we used uniform selection criteria (Log 2 FC ≥ 1, value of p ≤ 0.05) with a default redundancy removal setting for all the microarray data sets.…”
Section: Discussionmentioning
confidence: 96%
“…Only few exceptions such as the zed1-D mutant behave differently, possibly due to specific characteristics of the involved guardees. A recent meta-analysis of whole-genome shotgun (RNA-sequencing) data sets revealed that generally the expression of NLR genes is increased upon biotic stress (or treatment with SA) while their expression is mostly reduced under abiotic stress such as heat, but also drought or treatment with the phytohormone abscisic acid ( Yang et al, 2021 ). This could explain why NLR-dependent autoimmune phenotypes are generally reduced at higher temperatures and often depend on the availability of light.…”
Section: Modulation Of Autoimmunity By Environmental Conditionsmentioning
confidence: 99%
“…They are faced with various biotic stresses, including bacteria, fungi, viruses, herbivorous insects, and nematodes [1]. Moreover, abiotic stresses, such as salinity, drought, and extreme temperature, affect many physiological processes in plants [2]. The regulation of proper responses is crucial to reduce the damage caused by these stresses [3].…”
Section: Introductionmentioning
confidence: 99%